2021
DOI: 10.1371/journal.pntd.0009767
|View full text |Cite
|
Sign up to set email alerts
|

Multiple vector-borne pathogens of domestic animals in Egypt

Abstract: Vector Borne Diseases (VBDs) are considered emerging and re-emerging diseases that represent a global burden. The aim of this study was to explore and characterize vector-borne pathogens in different domestic animal hosts in Egypt. A total of 557 blood samples were collected from different animals using a convenience sampling strategy (203 dogs, 149 camels, 88 cattle, 26 buffaloes, 58 sheep and 33 goats). All samples were tested for multiple pathogens using quantitative PCR and standard PCR coupled with sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 120 publications
5
37
0
1
Order By: Relevance
“…Since 1966, many studies have stated the endemicity of piroplasmosis and anaplasmosis in several provinces in Egypt [ 27 , 28 , 29 ]. In accordance with our results, piroplasms ( T. annulata and B. bigemina ) in cattle were recorded in Al-Faiyum, Al-Beheira, Al-Giza, and Beni-Suef [ 4 , 22 , 27 , 30 ]. To our knowledge, piroplasmosis was detected for the first time among two cows in Matruh.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Since 1966, many studies have stated the endemicity of piroplasmosis and anaplasmosis in several provinces in Egypt [ 27 , 28 , 29 ]. In accordance with our results, piroplasms ( T. annulata and B. bigemina ) in cattle were recorded in Al-Faiyum, Al-Beheira, Al-Giza, and Beni-Suef [ 4 , 22 , 27 , 30 ]. To our knowledge, piroplasmosis was detected for the first time among two cows in Matruh.…”
Section: Discussionsupporting
confidence: 92%
“…By contrast, other studies have reported piroplasms in cattle from Al-Minufia [ 22 , 27 , 31 ]. In addition, piroplasmosis was detected in other provinces such as Gharbia [ 32 ], Port Said [ 33 ], Dakahlia [ 24 ], El-Wady El-Geded [ 3 , 4 ], Assiut and Kharga [ 34 ], and Qena [ 4 ]. Globally, theileriosis and babesiosis were detected in animals from different countries such as Pakistan [ 8 ], Brazil [ 9 ], Malaysia [ 10 ], and Mozambique [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations